[Letter by Susan Stuntz Updating Bob Lewis] (Tufts Archival Research Center, 2007)
Confidential; Memorandum from Susan Stuntz to Bob Lewis regarding the American Federation of Government Employees (AFGE) and their meetings with the Labor Management Committee.